Recontextualizing Islamic Education in the 21st Century, A Study on the Thought of KH. Ahmad Dahlan - Ikmah, Amit Dana; Al-Am, Maftah Rozani; Setiawati, Ika; Thoriqul Islam, Muhammad; Novitasari, Dwiana (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
KH. Ahmad Dahlan, founder of Muhammadiyah in 1912, was a prominent Islamic reformer whose educational vision emphasized the integration of religious and general sciences, moral development, and responsiveness to social change. This study aims to recontextualize his thoughts in the framework of 21st-century Islamic education, which demands critical thinking, creativity, collaboration, and digital literacy. Using a qualitative library research method, data were collected from books, journals, websites, and other credible sources. The analysis employed descriptive techniques to interpret Ahmad Dahlan’s educational philosophy. The findings highlight core components of his concept, including the definition, goals, methods, and materials of education, along with the roles of teachers and students. His holistic and progressive approach laid the foundation for competency-based Islamic education that embraces technology and character formation. In the modern context, his ideas remain highly relevant for shaping Islamic education that is inclusive, transformative, and rooted in the spirit of rahmatan lil-‘alamin.